Identifying Uses and Gratification Theory in the Digitalization of Da’wah: Existence and Transformation on Online Islamic Platforms in East Java - Fanani, AZ; Cahya Muslimah, Kiki (Institut Agama Islam Negeri (IAIN) Curup, 2025)
The rapid development of digital technology has reshaped Islamic communication by providing flexible access to religious knowledge and shifting traditional structures of authority. This study examines the relevance of Uses and Gratifications Theory in explaining the motivations of Muslim audiences in engaging with Muhammadiyah digital da’wah in East Java. This research applies a qualitative descriptive approach through documentation, observation, and textual analysis of official Muhammadiyah platforms such as tvMu, PWMU TV, pwmu.co, and PAI UMSurabaya Media during the period 2023 to 2024. The findings show that users demonstrate varied motivations aligned with key dimensions of the theory. These include the search for credible religious knowledge, appreciation of inspirational messages, expression of Islamic identity, participation in online religious communities, and efforts to obtain emotional comfort. Educational content through YouTube and website publications supports cognitive needs, while short video formats on emerging platforms strengthen emotional engagement and identity formation. Interactive features help build communal cohesion, affirming the emergence of digital religiosity. Although digital media democratizes access and expands the scope of da’wah, challenges remain, particularly the fragmentation of understanding and potential spread of inaccurate information. This study emphasizes the need for Muhammadiyah to strengthen participatory, creative, and multidimensional content in order to enhance digital literacy and sustain effective da’wah in contemporary society.